A Signification Analysis of Jiwa Toast Collaboration Poster: Culinary Commodification - Indah Septiar; Ahmad Jum’a Khatib Nur Ali (Universitas Syiah Kuala, 2025)
One of the culinary arts related to culture and creativity is bread. Bread making in Indonesia generally refers to the open-top bread from England which began to be popular in the 1800s. This type of bread is also commonly called white bread in Indonesia. This type of open-top bread is also known as sandwich bread in America after World War II. This type of bread has also become a cultural product that has become the cultural identity of England and America. This study focuses on how Jiwa Toast as an Indonesian brand builds a bread menu that is in accordance with Indonesian culture and commodifies culture through posters. This study uses a constructivist paradigm approach, with qualitative methods and theories of signification and habitus as analytical tools. The results of the study show that the collaborative advertising poster for the